The Association of Prenatal Tetanus, Diphtheria, and Acellular Pertussis (Tdap) Vaccination With Attention-Deficit/Hyperactivity Disorder. Issue 10 (7th May 2020) - Becerra-Culqui, Tracy A; Getahun, Darios; Chiu, Vicki; Sy, Lina S; Tseng, Hung Fu
Abstract: As prenatal vaccinations become more prevalent, it is important to assess potential safety events. In a retrospective cohort study of Kaiser Permanente Southern California (Pasadena, California) mother-child pairs with birth dates during January 1, 2011–December 31, 2014, we investigated the association between prenatal tetanus, diphtheria, and acellular pertussis (Tdap) vaccination and risk of attention-deficit/hyperactivity disorder (ADHD) in offspring. Information on Tdap vaccination during pregnancy was obtained from electronic medical records. ADHD was defined by International Classification of Diseases codes (Ninth or Tenth Revision) and dispensed ADHD medication after age 3 years. Children were followed to the date of their first ADHD diagnosis, the end of Kaiser Permanente membership, or the end of follow-up (December 31, 2018). In Cox proportional hazards models, we estimated unadjusted and adjusted hazard ratios for the association between maternal Tdap vaccination and ADHD, with inverse probability of treatment weighting (IPTW) used to adjust for confounding. Of 128, 756 eligible mother-child pairs, 85, 607 were included in the final sample. The ADHD incidence rate was 3.41 per 1, 000 person-years in the Tdap-vaccinated women and 3.93 per 1, 000 person-years in the unvaccinated (hazard ratio = 1.01, 95% confidence interval: 0.88, 1.16). The IPTW-adjusted analyses showed no association between prenatal Tdap vaccination and ADHD in offspring (hazard ratio = 1.00, 95% confidence interval: 0.88, 1.14). In this study, prenatal Tdap vaccination was not associated with ADHD risk in offspring, supporting recommendations to vaccinate pregnant women.